The interim application of EOT from 18 June , 2018 to 15 July 2018 - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding the interim application of EOT from 18 June , 2018 to 15 July 201 May of Brac University new campus development project .